Egyptian Energy Sector between 2004 to 2024 in the Context of Transition to Renewables - Khedr, Adam Hossameldin Hassan Ahmed; De Castro, Tereza; Bok, Martin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examines the transformation of Egypt's energy sector from 2004 to 2024, analyzing the country's shift from fossil fuels to renewable energy sources. Through a review of key policy reforms, major mega projects, and the evolving energy mix, the research assesses the drivers and impediments of this transition. The findings indicate that while post-2014 reforms such as subsidy removal and competitive tendering, have successfully intensified large-scale renewable investments like the Benban Solar Park, yet significant challenges remain. These include fragmented governance, high capital costs, and grid integration issues. The study identifies emerging opportunities in green finance and hydrogen production as critical for future growth. It concludes that achieving Egypt's ambitious Vision 2030 renewable energy targets hinges on intensive institutional modernization and heavy investments in grid infrastructure to unlock its full sustainable potential and solidify its role as a regional energy leader.
Vedoucí práce: Tereza De Castro
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses